Linhas e nós no acesso aos serviços de saúde pelas pessoas com deficiência - um olhar para educação - Sarturi, Fernanda (2018)
Disability has been gaining space in health research, resulting in reflections about the health care formation in order to help these users. This research was aimed to understand the current barriers in the access by people with disabilities to the health care services in Palmeira das Missões/RS through the view of health workers. It is an exploratory and descriptive field research with a quantitative-qualitative approach. Data collection has occurred in two steps, the first through a self-administered questionnaire and the second through a focus group discussion. The study scenery was composed by ninet health care services in Palmeira das Missões/RS, including basic and hospital health care. The first and the second steps were composed by 110 and 14 health care workers, respectively. It can be highlighted that the ethical precepts and legal affairs were respected in this research. Data was typed and analyzed in Microsoft Excel® to obtain the quantitative analysis, after it was conducted the descriptive analysis, with percentage calculus and confidence interval of 95%. Correlation between variables was performed through the program Statistical Package for the Social Sciences, using the chi-square test. Qualitative data was subjected to a Content Analysis proposed by Bardin. These results were discussed under the dialectics in order to understand the choice of movement of the research method and political, social and cultural foundation of this research. Results show a group of 80% of female workers, average age of 40,9 years old, average time working of 10,4 years, 71,3% do not participate of the Programa de Educação pelo Trabalho – Redes de Atenção, the major number was of nursing technicians (38,5%). Regarding the fact of receiving information about people with disabilities during their formation, 66,1% said that they have not received any information and 65,1% said that they have not received information during their professional performance either. About assisting these users, 90% have assisted patients in the last three months, most of them people with mental disability – 76,5%, and 78,7% of the cases have occurred in service. To these workers, the health care unit where they work assist people with disabilities (97,2%) with an average of 57,2% of attendance each trimester. It can be observed a statistically significant difference in participating of the Programa de Educação pelo Trabalho – Redes de Atenção and receiving formation during their professional performance, about receiving information and feeling able to work there was not a significant difference, could be stated that these information might not be enough to assist these people with disabilities. Emerged from this research two categories – Permanent education as a strategy to minimize the barriers in accessing the health care services by people with disabilities and Primary Care Attention network to people with disabilities - untying knots in the interlacing threads. It was possible to contrast the disposed between the current legislation, theoretical material about the theme and the reality of the health care service. This movement allowed the discussion under the dialectics the perspective of the health workers about the barriers in accessing the health services by people with disabilities. By the end of this study, it can be said that the restrict knowledge about these users since the formation, the lack of investment by the management, the bureaucratic obstacles and the current dynamic in Primary Care Attention Network to people with disabilities are the main barriers to access the health services in Palmeira das Missões recognized by health workers. After elucidating the objectives of this research, it has as a suggestion to develop research and extension actions that may minimize the access the health services by people with disabilities.